Desenvolvimento de um sistema de gerenciamento da manutenção suportada pela engenharia da confiabilidade - Pereira, Fernando Henrique Gomes (2018)
With the evolution of technology, means of production and manufacturing processes, 5the maintenance is nowadays as a department within companies to add value to the product. In this context, aligned with Asset Management, Reliability Engineering and a set of methodologies that make up are in evidence in order to seek an ample operational availability. Thereat, Maintenance and Asset Management software gains a new status. Make sure that failures and generating orders services are registered are no longer enough to meet current demands. Therefore, Reliability Engineering software concepts into a single platform is the first step in managing business assets with excellence. Therefore, the present work has proposed to develop a tool to join the methodologies of Maintenance Engineering and Reliability Engineering usingMicrosoft Excel® as working interface and VBA (Visual Basic for Applications) as programming language. It was possible to develop work order routines, faults log and put all equipment in the system. This information can be used as a database for the Reliability module, where the methodologies of Life Data Analysis and Reliability Block Diagrams have been developed. From a case study, It was obtained an error in the estimation of the shape parameter β and scale parameter η from the Weibull distribution of the order of 0.0032% and 0.0397%, respectively, when compared to a Reliability Software.